Workplace spirituality among Malaysian community service employees in the public sector - Ahmad, Aminah; Omar, Zoharah (Canadian Center of Science and Education, 2016)
Despite the number of individuals who engage in pursuits for spirituality in their daily lives, there is still lack of studies examining spirituality in the workplace especially in the public sector. This study explored the experience of spirituality at the workplace among community service employees in a public sector organization. The dimensions of spirituality studied include meaningful work, sense of community and alignment of individual values with organizational values. Survey data from 180 community service employees revealed that overall the employees experienced a reasonably high level of spirituality, and employees experienced meaningfulness of work more as compared to the sense of community, and alignment of values. The results imply that the community service organization studied serves as a favorable environment that fosters the experience of spirituality among its employees. Though limited by the monosectoral nature of this investigation and the Eastern context, future researchers are encouraged to compare employees’ experiences in workplace spirituality in both the public and private service sectors as well as in both the Eastern and Western contexts.